Efeitos ocasionados pela deficiência e excesso de lítio nas propriedades estruturais e ópticas do composto LiAl5O8 dopado com cério, európio ou térbio - Silva, Ariosvaldo Junior Sousa (2017)
The study describes the preparation, structural and optical characterization of Lithium Aluminate (LiAl5O8) pristine and doped with trivalent lanthanide ions (Ln3+ =Ce3+, Eu3+ or Tb3+). In this study, Lithium Aluminate pure and doped were produced via sol-gel route, using glucose anhydrous as polymer agent. Structural analysis was performed using X-rays di raction (XRD) and optical properties through photoluminescence spectroscopy. The X-ray di raction (XRD) patterns showed signi cant evidence of formation of the desired crystalline phase. Based on XRD patterns and using the Scherrer equation, it is estimated that all of the samples produced have a nanosize dimensions. The results revels stoichiometric variation of lithium and the incorporation of the dopant ion did not cause signi cant changes in the LiAl5O8. Photoluminescence measurement of (LiAl5O8) pristine and doped with Ce3+, Eu3+ or Tb3+, for samples with and without variation of lithium stoichiometry were performed. The Excitation and emission spectra of the LiAl5O8 pristine showed with wide and high intensity bands, all attributed to the Fe3+ ion. The presence of iron ions are attributed to its existence in precursor reagents. Excitation spectra of Ce3+, Eu3+ or Tb3+, have high intensity wide band and wavelengths of higher excitation intensity in the ultraviolet region (240-290 nm), all attributed the speci c intercon guration transitions of each dopant ion. Being for the ions Ce3+ and Tb3+ due to the transition 4f!5d, and for the ion Eu3+ due to the charge transfer between Oxygen and Europium. The emission spectra, exhibited high emission intensity in the blue colors when doped with Ce3+ ions, red when doped with Eu3+ ions and green with Tb3+ ions. Based on the emission spectra and chromaticity diagrams, it was possible to verify that the accomplishment of the stoichiometric variation of Lithium in uences quantitatively in the spectral emission, motivating a variation in the chromaticity coordinates. Therefore, it can conclude that the variation of the Lithium stoichiometry signi cantly changes the optical properties of the LiAl5O8 when doped Ce3+, Eu3+ or Tb3+. This is capable to emitting di erent color bands in the region of blue, red and green when exposed to ultraviolet radiation.